Beyond the Implant: Retrieval Analysis Methods for Implant Surveillance 2018
DOI: 10.1520/stp160620170095
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Material Loss from Femoral Stem Taper Surfaces through Development of a Responsive Morphological Filtering Technique

Abstract: The presence of taper junctions in hip arthroplasty designs has been suggested to contribute to premature clinical failure, in part due to corrosion-assisted material loss. Characterization of the material loss at the taper junction is an important factor in determining not only taper performance but also the requirement for revision of primary stems. It is therefore clear that a robust metrological solution to this issue is required to understand the connection between damage to the stem surface and explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Where a smooth taper would be reconstructed by performing linear interpolation between areas not exhibiting damage, it is not possible to use this approach on microgrooved stem tapers. An alternative approach is required whereby the microgroove texture of a user identified 'as manufactured' area is mathematically modelled and evaluated over the remaining taper length, producing a reconstruction of the pre-implantation geometry [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Where a smooth taper would be reconstructed by performing linear interpolation between areas not exhibiting damage, it is not possible to use this approach on microgrooved stem tapers. An alternative approach is required whereby the microgroove texture of a user identified 'as manufactured' area is mathematically modelled and evaluated over the remaining taper length, producing a reconstruction of the pre-implantation geometry [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…For type B tapers, studies have utilised the same cylinder mapping strategy [12,21,59,82,91], but reported challenges with workpiece alignment due to the influence of texture on centring and levelling algorithms. [59,91].…”
Section: Roundness Measurement Machinesmentioning
confidence: 99%
“…For type B tapers, studies have utilised the same cylinder mapping strategy [12,21,59,82,91], but reported challenges with workpiece alignment due to the influence of texture on centring and levelling algorithms. [59,91]. This can be overcome by exploiting the mechanical filtering effect of a larger spherical stylus during alignment [66,91].…”
Section: Roundness Measurement Machinesmentioning
confidence: 99%
See 2 more Smart Citations